2013
DOI: 10.3390/ijerph10041342
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Willingness to Pay to Prevent Child Maltreatment Deaths in Ecuador and the United States

Abstract: Estimating the benefits of preventing child maltreatment (CM) is essential for policy makers to determine whether there are significant returns on investment from interventions to prevent CM. The aim of this study was to estimate the benefits of preventing CM deaths in an Ecuadorian population, and to compare the results to a similar study in a US population. The study used the contingent valuation method to elicit respondents’ willingness to pay (WTP) for a 1 in 100,000 reduction in the risk of CM mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The CV method assumes that the variable Y i represents the WTP for testing of person i with characteristics X i , following the model [ 32 ]: where ε i has a normal distribution with a mean of zero. Since we observe respondents’ WTP indirectly via their responses to the CV questions, we know the value of Y i to lies within the interval [ Y i1 ; Y i2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CV method assumes that the variable Y i represents the WTP for testing of person i with characteristics X i , following the model [ 32 ]: where ε i has a normal distribution with a mean of zero. Since we observe respondents’ WTP indirectly via their responses to the CV questions, we know the value of Y i to lies within the interval [ Y i1 ; Y i2 ].…”
Section: Methodsmentioning
confidence: 99%
“…The DBDC-OE approach enhances the accuracy of WTP estimates, relative to the DBDC approach alone. Previous literature has suggested that DBDC-OE has a lower magnitude of starting point bias and incentive incompatibility than DBDC alone [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The four papers in the field of health that empirically valued interventions increasing health safety, all used a form of stated preference methodology. These papers aimed to estimate the value of reducing mortality risks [6], preventing child maltreatment deaths [7], reducing the risk of sexually transmitted diseases [8] and vaccinations in pandemic outbreaks [9]. The first three papers used willingness to pay (WTP) contingent valuation method, while the last paper used a discrete choice experiment to elicit valuations.…”
Section: Introductionmentioning
confidence: 99%
“…Dichotomous choice questions can be broken down into single- or double-bounded questions, where a double-bounded question means that, after being given an initial ‘yes or no’ WTP price, as in a single-bounded question, the respondent is then given a second WTP option dependent on his first answer [32]. The most popular question format of the 22 papers is an open-ended question (48%) [11, 15, 16, 19, 27, 29, 30, 33, 47], followed by dichotomous choice [1, 15, 17, 26, 40, 47, 54, 55] (35%), and payment card [3337]. Two of the papers use both open-ended questions and dichotomous choice [15, 47].…”
Section: Resultsmentioning
confidence: 99%